2013
DOI: 10.1371/journal.pone.0076008
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Changes in Circulating and Intestinal γδ T Cell Subsets, Invariant Natural Killer T Cells and Mucosal-Associated Invariant T Cells in Children and Adults with Coeliac Disease

Abstract: Coeliac disease is a chronic small intestinal immune-mediated enteropathy precipitated by exposure to dietary gluten in genetically predisposed individuals. The only current therapy is a lifelong gluten free diet. While much work has focused on the gliadin-specific adaptive immune response in coeliac disease, little is understood about the involvement of the innate immune system. Here we used multi-colour flow cytometry to determine the number and frequency of γδ T cells (Vδ1, Vδ2 and Vδ3 subsets), natural kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 49 publications
4
88
1
1
Order By: Relevance
“…Given the known role of MAIT cells in responding to riboflavin‐synthesizing microbes it is also possible that MAIT cell recruitment and activation is a consequence of the dysbiosis of the gastrointestinal microbiome that occurs in inflammatory bowel disease 57, 58. By contrast, human lamina propria and blood V α 7.2 + CD161 + MAIT cells are deficient in untreated coeliac disease,59 another important autoimmune enteropathy 60. Coeliac disease is driven by exposure to dietary gluten in genetically predisposed people, but it can be associated with compromised mucosal barrier function and bacterial overgrowth and therefore has the potential for activation‐induced MAIT cell death 59…”
Section: Observations From Specific Diseasesmentioning
confidence: 99%
“…Given the known role of MAIT cells in responding to riboflavin‐synthesizing microbes it is also possible that MAIT cell recruitment and activation is a consequence of the dysbiosis of the gastrointestinal microbiome that occurs in inflammatory bowel disease 57, 58. By contrast, human lamina propria and blood V α 7.2 + CD161 + MAIT cells are deficient in untreated coeliac disease,59 another important autoimmune enteropathy 60. Coeliac disease is driven by exposure to dietary gluten in genetically predisposed people, but it can be associated with compromised mucosal barrier function and bacterial overgrowth and therefore has the potential for activation‐induced MAIT cell death 59…”
Section: Observations From Specific Diseasesmentioning
confidence: 99%
“…As a flip side of the potential benefit of the adjuvant properties of Vc9/Vd2 T cells, a dysregulated generation of APCs under the influence of Vc9/Vd2 T cells may eventually result in uncontrolled inflammation and the generation of cellular and humoral autoimmune responses, thereby contributing to the clinical symptoms in scenarios such as psoriasis [226], inflammatory bowel disease [227], celiac disease [196,228], and multiple sclerosis [229]. More research is clearly needed to delineate the complex interactions of Vc9/Vd2 T cells (and other unconventional T cells) with different immune and non-immune cells, both locally and systemically, and define how such knowledge can be exploited for therapeutic interventions to either boost protective immune responses or suppress excessive inflammation.…”
Section: Innate Regulation Of Adaptive Immune Responses: Vd2 + Versusmentioning
confidence: 99%
“…Of notable exception is the finding of human CD1-restricted T cells with semi-invariant TCRs within the cd T cell repertoire. Whilst Vc9/Vd2 T cells make up the majority of peripheral human cd T cells, Vd1 + and Vd3 + ('Vd2 neg ') T cells are the predominant cd T cell subtypes in human intestine and liver [196,197]. Several studies have demonstrated CD1a, CD1b, CD1c and CD1d reactivity of human Vd1 + T cells [198][199][200][201][202][203] and CD1d-reactivity of human Vd3 + T cells [204].…”
mentioning
confidence: 99%
“…Expression of these proteins may in turns enhance the protection and accelerate healing of cellular damage, implying the tissue protective functions of MAIT cells [49] . Numerous studies have reported possible implications of MAIT cells in psoriasis [51] , celiac disease [52] , systemic lupus erythematosus [53] , diabetes [54,55] and obesity [55,56] . In our recent study, MAIT cells were shown to be useful to distinguish diseases that manifest similar symptoms such as fibromyalgia syndrome, rheumatoid arthritis, and spondyloarthritis by measuring the expression of cell surface antigens, in particular, chemokine receptors associated with homing [57] .…”
Section: Mait Cells In Health and Diseasesmentioning
confidence: 99%